The Contribution of Feminism to Contemporary Public Debates About Law - Barker, Nicola; Ring, Sinead; Drakopoulou, Maria; Hunter, Rosemary (feminists@law, 2014)
This is the audio recording of a panel session at the Kent Critical Law Society conference held at the University of Kent on 1 March 2014. Nicola Barker speaks on 'Feminism, Family and the Politics of Austerity' (with accompanying powerpoint slides); Sinead Ring speaks on 'The Pernicious Nature of Rape Myths and How They Continue to Affect Rape Prosecutions'; Maria Drakopoulou speaks on 'Feminism, Tradition and the Question of Sexual Violence'; and Rosemary Hunter acts as discussant, commenting on all three papers.